Strategic Groups and the Structure-Performance Relationship - Newman, Howard H. (The Review of Economics and Statistics, 1978)
STATISTICAL analyses of the structureperformance relationship in manufacturing industries have invariably assumed that an industry's member firms differ only in their market shares. This paper demonstrates that this assumption is often incorrect, and that the complexity of the structure of strategic groups populating an industry exerts a significant influence on its performance. In the following sections we explain the sources and significance of strategic groups, derive hypotheses about their influence on an industry's profitability, and test these hypotheses on a sample of producer-good industries.